HISTORICAL-LEGAL RELATIONS BETWEEN THE SERBIAN ORTHODOX CHURCH AND THE MACEDONIAN ORTHODOX CHURCH UNTIL TODAY - Perić, Miodrag (Political Review, 2023)
In the first part of the work, the author talks about the unilateral declaration of the Macedonian Orthodox Church as autocephalous at the third Macedonian Church-Peoples Assembly on Julu 18, 1967, and the church of “St. Clement” in Ohrid and denying the autocephaly of the MPC from its Mother Church, the Serbian Orthodox Church. In the second part of the paper, the author talks about the donation of autocephaly by the Holy Council of Bishops of the Serbian Orthodox Church to the Macedonian Orthodox Church-Ohrid Archdiocese. The decision on the autocephaly of the MPC-OA was solemnly and administratively ci+onfirmed at the Holy Liturgy in the Cathedral Church in Belgrade on June 5, 2022, by awarding the Tomos on Autocephaly-Macedonian Orthodox Church-Ohrid Archdiocese from the hands of His Holiness Serbian Patriarch Porfirije (Perić) to the head of the MPC-OA Archibishop of Ohrid and Macedonia Stefan (Veljanovski). The author of the paper argues the point of view that the recognition of the autocephaly of the Macedonian Orthodox Church-Ohrid Archdiocese is historically and canonically valid and that it is significant both for thr Orthodoxy oh the Balkans and beyond as well as for the collective national Macedonian identity and the further affirmation of North Macedonia as a sovereign state with international legal subjectivity.